Endoscopic full-thickness resection of sigmoid colon cancer in a liver recipient - M. T. Bekov; A. R. Monakhov; K. S. Smirnov; Ya. S. Yakunin; R. A. Latypov; D. O. Oleshkevich; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2024)
Compared with the general population, solid organ transplant recipients have a higher cancer risk. This is mainly due to the use of immunosuppressive therapy. Colorectal cancer is one of the most common cancers in recipients. This paper presents the experience of endoscopic full-thickness resection (EFTR) of a sigmoid colon cancer in a liver recipient.